Effect of Thyroxine Hormone by Oral on Growth and Survival Rate of Coral Platy Xiphophorus maculates - Junior, M. Zairin; Pahlawan, R.G.; Raswin, M. (Jurnal Akuakultur Indonesia, 2005)
Thyroxine is known as a hormone that can affect growth of fish by increasing the metabolic rate, feed efficiency and protein retention.  In this study, effect of thyroxine administration through feed on growth and survival of coral platy fish (Xiphophorus maculatus) was observed.  Dosage of thyroxine used was 0.2, 2 and 20 mg/kg of feed, and were combined with duration time of treatment i.e. 1, 2 and 3 weeks.  All treatments were performed triplicate.  The results of study show that higher growth in length (21.3 mm) and weight (244.5 mg) was obtained by administration of 20 mg thyroxine per kilogram of feed for two weeks and this treatment had no effect on the survival rate of coral platy fish Keywords: coral platy, Xiphophorus maculatus, tyroxine, growth   ABSTRAK Tiroksin diketahui sebagai hormon yang dapat mempengaruhi pertumbuhan dengan jalan meningkatkan laju metabolisme tubuh, efisiensi makanan dan retensi protein. Pada penelitian ini dipelajari pengaruh pemberian hormon tiroksin melalui pakan terhadap pertumbuhan dan kelangsungan hidup ikan plati koral (Xiphophorus maculatus). Dosis tiroksin yang digunakan yaitu 0,2; 2 dan 20 mg/kg pakan, dan dikombinasikan dengan lama waktu perlakuan satu, dua dan tiga pekan. Semua perlakuan diulang tiga kali. Hasil penelitian menunjukkan bahwa pemberian hormon tiroksin sebesar 20 mg/kg pakan selama dua pekan memberikan pertumbuhan panjang dan pertambahan berat terbaik masing-masing 21,3 mm dan 244,5 mg dan tidak berpengaruh terhadap kelangsungan hidup ikan platy koral. Kata kunci: ikan plati koral, Xiphophorus maculatus, tiroksin, pertumbuhan